1997
DOI: 10.1074/jbc.272.7.4549
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Sialidase Encoded in the Human Major Histocompatibility Complex

Abstract: Mammalian sialidases are important in modulating the sialic acid content of cell-surface and intracellular glycoproteins. However, the full extent of this enzyme family and the physical and biochemical properties of its individual members are unclear. We have identified a novel gene, G9, in the human major histocompatibility complex (MHC), that encodes a 415-amino acid protein sharing 21-28% sequence identity with the bacterial sialidases and containing three copies of the Asp-block motif characteristic of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 66 publications
2
88
0
Order By: Relevance
“…Recent cDNA cloning for human lysosomal neuraminidase has revealed that it encodes a 45-kDa protein with three potential N-linked glycosylation sites (Bonten et al 1996;Pshezhetsky et al 1997;Milner et al 1997). This information has facilitated the identification of gene mutations causing sialidosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent cDNA cloning for human lysosomal neuraminidase has revealed that it encodes a 45-kDa protein with three potential N-linked glycosylation sites (Bonten et al 1996;Pshezhetsky et al 1997;Milner et al 1997). This information has facilitated the identification of gene mutations causing sialidosis.…”
Section: Discussionmentioning
confidence: 99%
“…According to the sequence alignment (Milner et al 1997), we built a model of the human lysosomal neuraminidase without the N-terminal 47 residues, corresponding to the signal peptide (Milner et al 1997;Vinogradova et al 1998). The model was, thus, composed of the 368 amino acids from residue 48 to the terminal residue 415, the amino acid sequence homology with the aligned fragment of Salmonella typhimurium LT2 being 39.7%.…”
Section: Structural Modeling Of Wild-type and Mutant Lysosomal Neurammentioning
confidence: 99%
See 1 more Smart Citation
“…Cathepsin A was cloned and its mutations in galactosialidosis were first characterized 15 years ago [Galjart et al, 1988], but cloning of sialidase has been hampered for almost two decades by the low tissue content and instability of this enzyme. Three groups simultaneously identified the human sialidase cDNA and gene by a homologous search in the Expressed Sequence Tags Database (dbEST, National Center for Biotechnology Information) and direct sequencing of human chromosome 6 [Bonten et al, 1996;Milner et al, 1997;Pshezhetsky et al, 1997]. These studies paved the way for the characterization of the molecular basis of sialidosis.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the human lysosomal sialidase gene has been cloned (Bonten et al 1996;Pshezhetsky et al 1997;Milner et al 1997) on the basis of the genomic and structural information on the sialidases obtained from a variety of species, including viruses and bacteria (Roggentin et al 1989;Rothe et al 1991;Crennell et al 1993Crennell et al , 1994Gaskell et al 1995). The human sialidase cDNA contains a 1.2-kb open reading frame and a polyadenylation site within the 3袌 untranslated region.…”
Section: Introductionmentioning
confidence: 99%